"In war or in peace:" The technological promise of science following the First World War1. (August 2017) - Katzir, Shaul
Abstract : Following World War One, powerful groups in society substantially raised their expectations of the natural sciences. Scientific research became a promise for transformations in technology, and consequently in the economy and society. While this expectation was not completely new, before the war the potential benefits of scientific research to answer practical technological problems had been fiercely contested. During the war, scientists were mobilized to military related research only gradually due to a combination of technological challenges and the efforts of science advocates. The significant success of much military research convinced many erstwhile skeptics that science and research could be of practical value for technology and society, as well as the military. Science promised technological and economic growth, but the promise entailed also a threat from its inappropriate use, and from its use by one's competitors. The threat of competition was especially strong at the international level. Policy makers emphasized that investment in science is crucial for "the economic struggles of peace‐time." The promise and threat alike led to an increase in science funding, and the establishment of special governmental, military, and commercial institutions for the fostering of science and its application to technology. Scientists themselves also altered their view of their disciplines.